(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: Dysmenorrhea is one of the most prevalent adolescent health problems. Aim . This study aimed to evaluate the impact of primary dysmenorrhea on the level of physical activity among female students at the College of Applied Medical Sciences, Jouf University. Method: A cross-sectional study was conducted in this study. Purposive sampling technique was used to enroll seventy-nine female students who reported moderate to severe pain and recruited from Physiotherapy and Health Rehabilitation Department from the middle of April to the end of August. A self-administered questionnaire, was designed to collect required data in this research. Results: from the present study showed that there was a significant impact of pain on the absenteeism, low concentration, poor academic performance, and reduced physical activity. All those effects were accompanied by higher pain rating scale (p-value 0.0001, 0, 0001, 0.011and 0.023 respectively). Conclusion: Most of the female students had experienced a variety of dysmenorrhea degrees that may have an adverse effect on the number of physical activity limitations and other variables such as absenteeism, low concentration, and poor academic performance.